STRUKTUR MIKROSKOPIS KARTILAGO EPIFISIALIS TIBIA FETUS MENCIT (Mus musculus L.) DARI INDUK DENGAN PERLAKUAN KAFEIN - Heri Budi Santoso (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2006)
Caffeine affects activity of enzyme of polimerase DNA, induce the mitosis of cells mammal of before replication DNA ended the perfection, and also pursue the activity of enzyme fosfodiesterase is hence anticipated by a potential caffeine generate the developmental defect, for example can pursue the process of ossification endochondralis in growth plate. This present research studied the effect of caffeine gift by oral on pregnant dam during organogenesis to structure of histologi growth plate tibia foetus. Twenty four pregnant mice (6 per group) were treated by gavage with 0 (control), 40, 80, 120 mg/kg b.w caffeine from gestation day 6 to 15. On day 18 of pregnancy, fetuses was removed from dams by caecarean section.. Observation of histological structure of the tibial growth plate preparation by paraffin method (Hematoxylin-Eosin staining). The result showed that caffeine cause slightened proliferative zone, maturation zone, and cartilage calcification zone on the mouse tibial growth plate.